The Impact of Hadith Memorization Program Management on the Religious Character of Students at Islamic Boarding Schools - Miftah Nurul Ma'arif (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
This study aims to determine the influence and contribution of the management of the hadith memorization program on the religious character of students at the Miftahul Falah Cantigi Islamic Boarding School, Cikalong, Tasikmalaya. This study uses a quantitative approach with an ex post facto method. A sample of 52 students was determined using the Slovin formula from a population of 110 people, with a probability sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression with the help of SPSS version 27. This study encourages Islamic boarding school managers to develop a professional and sustainable hadith memorization program. These findings can also be a reference for educational institutions and related agencies in developing a character education model based on Islamic values. The uniqueness of this study lies in the quantitative measurement of the management of the hadith memorization program, not the Al-Quran memorization, and its relationship with the religious character of students in the context of Islamic boarding school education. The results of the analysis indicate that the management of the hadith memorization program has a positive and significant effect on the religious character of students, with a significance value of 0.001 (<0.05). The coefficient of determination (R²) of 0.388 indicates that 38.8% of the variation in religious character is explained by program management, while the remainder is influenced by other factors. The program, which is implemented in a structured and efficient manner, has been proven to strengthen the students' faith, worship, morals, and socio-religious life.